Analisis Minat Belajar Matematika Siswa Pada Pembelajaran Daring dikelas IV Sekolah Dasar - Afrianti, Indah; Tiurlina, Tiurlina; Alfarisa, Fitri (Didaktika, 2021)
The background of this research was made after the arrival of the covid-19 virus outbreak which caused changes in the learning system. Interest has a great meaning in learning activities because interest has a very large role in supporting success. Someone will be successful when interested in something that is being studied and will automatically show their activeness in participating in learning. Therefore, it is important to find out around the categorization of students' interest in learning, especially in learning mathematics. This study uses a quantitative style with a quantitative descriptive method. The sample in this study was the fourth-grade elementary school students totaling 40 people. The descriptive method consists of describing students' interest in learning mathematics in the current online learning situation. The instrument used by researchers in collecting data is in the form of questionnaires and interviews. The study revealed that the online learning process was carried out using the WhatsApp application media. The use of WhatsApp is used to adjust the ability of teachers and school policy agreements. The learning process takes place quite effectively and is easy to reach by teachers, students, and parents. Then it is seen that the interest in learning mathematics in online learning is very diverse. There is very high interest in learning as many as 16 students (40%), quite high interest in learning as many as 18 (45%) students, high interest in learning as many as 5 (12.5%) and those who have a very low interest are 4 students (2,5%).